Psychosocial Impact of Living with a Stuttering Disorder: Knowing Is Not Enough - Beilby, Janet (Thieme Medical Publishers, 2014)
Stuttering requires a multidimensional perspective given that, in recent years, researchers have shown the impact of the disorder to reach far beyond the surface components with demonstrated psychosocial and anxiety effects for the individual living with a stutter. This article explores the impact a stuttering disorder has on the individual (child, adolescent, and adult) and on their family members (siblings, parents, and partners). These experiences include behavioral and social difficulties, self-awareness, reactions to stuttering, communication difficulties in daily situations, and overall quality of life. The influence of stuttering on the most intimate relationships of the person who stutters is presented. An overview of stuttering across the life span is discussed in terms of stuttering in children and adolescents, and the significant levels of adverse impact as a result of living with a stutter are described. In addition, the impact that the stuttering disorder has on the parents and siblings of children who stutter is also detailed through significant findings pertaining to lack of attachment and trust between the young people and their parents. The responsibilities and demands on parents and siblings in the family context are highlighted. Focus is also placed on the experience of living with a person who stutters from the perspective of their life partner. Perceived quality of life is explored with unexpected differences recounted between the quality of life experienced by the adult who stutters and their partner’s perceptions of this disorder. Finally, the potential for a novel Acceptance and Commitment Therapy for individuals who stutter is presented.